Surfactant proteins in pediatric interstitial lung disease - Griese, Matthias; Schaible, Thomas (Pediatric research, 2016)
Background: Children’s interstitial lung diseases (chILD) comprise a broad spectrum of diseases. Besides the genetically defined surfactant dysfunction disorders, most entities pathologically involve the alveolar surfactant region, possibly affecting the surfactant proteins SP-B and SP-C. Therefore, our objective was to determine the value of quantitation of SP-B and SP-C levels in bronchoalveolar lavage fluid (BALF) for the diagnosis of chILD. Methods: Levels of SP-B and SP-C in BALF from 302 children with chILD and in controls were quantified using western blotting. In a subset, single-nucleotide polymorphisms (SNPs) in the SFTPC promoter were genotyped by direct sequencing. Results: While a lack of dimeric SP-B was found only in the sole subject with hereditary SP-B deficiency, low or absent SP-C was observed not only in surfactant dysfunction disorders but also in patients with other diffuse parenchymal lung diseases pathogenetically related to the alveolar surfactant region. Genetic analysis of the SFTPC promoter showed association of a single SNP with SP-C level. Conclusion: SP-B levels may be used for screening for SP-B deficiency, while low SP-C levels may point out diseases caused by mutations in TTF1, SFTPC, ABCA3, and likely in other genes involved in surfactant metabolism that remain to be identified. We conclude that measurement of levels of SP-B and SP-C was useful for the differential diagnosis of chILD, and for the precise molecular diagnosis, sequencing of the genes is necessary.